Doktrin Kristus (Kristologi) - Mery Cyntia; Prisna Pritalora; Ronald Evandi Aden (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
In an increasingly complex world full of diverse beliefs, the search for meaning and truth has never been more important. Since the early days of Christianity, theologians and thinkers have sought to understand and explain the nature of Christ. By understanding Christology, we not only gain insight into who Jesus is, but also how His teachings can provide guidance in facing the challenges of everyday life. Christology is a branch of theology that focuses on the study of Jesus Christ, specifically who He is, what His nature and office are and how redemption is accomplished by Christ, in His nature and His role in saving humanity. Christology is not just a religious study, but also a way of strengthening faith, strengthening hope, and living a spiritual life that is connected to Christ. Therefore, a deep understanding of Christ is essential for Christians to understand their faith.